Incidence of Paralympic sports injuries in para athletes: systematic review - Vitasari, L.; Perdana, S. S.; Azizah, A. N. (Advances in Health Sciences Research, 2023)
Paralympic is the term referred to as an international sports competition for top athletes with disabilities who have experienced increased participation and development in sports. Consequently, it is difficult to understand injury patterns in the winter and summer Paralympics due to the rapid evolution of sporting events. The purposes of this research were to identify the overall injury incidence rate based on gender, age, anatomical region, sport, competition season, and injury onset, or what can be called the pattern of sports injury in para-athletes at the winter paralympics and summer paralympics. This systematic review research was obtained through four databases, namely PubMed, Google Scholar, Scopus, and Science Direct. Assessment of article quality employed the Newcastle-Ottawa Scale (NOS) and then obtained six articles involving a population of paralympic para-athletes. Four articles represent injury rates for the winter Paralympics, and the other two are for the summer Paralympics. The results showed that the highest injury incidence rate was in men aged 35 years, shoulder area, competition period, and with acute traumatic injuries. There were developments and differences in sports in the winter paralympic and summer paralympic, therefore the incidence rate shown varies based on each paralympic season. However, 5-side football in the summer Paralympics and alpine skiing in the winter Paralympics are the sports that consistently show the highest number of injuries in every Paralympic match. Differences in outcome measures and heterogeneity in para-athletes and sports were set as the limitations of this study.